If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -4) + -1(3 + -2x) = (3x + 4) + -1(6 + x) Reorder the terms: (-4 + x) + -1(3 + -2x) = (3x + 4) + -1(6 + x) Remove parenthesis around (-4 + x) -4 + x + -1(3 + -2x) = (3x + 4) + -1(6 + x) -4 + x + (3 * -1 + -2x * -1) = (3x + 4) + -1(6 + x) -4 + x + (-3 + 2x) = (3x + 4) + -1(6 + x) Reorder the terms: -4 + -3 + x + 2x = (3x + 4) + -1(6 + x) Combine like terms: -4 + -3 = -7 -7 + x + 2x = (3x + 4) + -1(6 + x) Combine like terms: x + 2x = 3x -7 + 3x = (3x + 4) + -1(6 + x) Reorder the terms: -7 + 3x = (4 + 3x) + -1(6 + x) Remove parenthesis around (4 + 3x) -7 + 3x = 4 + 3x + -1(6 + x) -7 + 3x = 4 + 3x + (6 * -1 + x * -1) -7 + 3x = 4 + 3x + (-6 + -1x) Reorder the terms: -7 + 3x = 4 + -6 + 3x + -1x Combine like terms: 4 + -6 = -2 -7 + 3x = -2 + 3x + -1x Combine like terms: 3x + -1x = 2x -7 + 3x = -2 + 2x Solving -7 + 3x = -2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + 3x + -2x = -2 + 2x + -2x Combine like terms: 3x + -2x = 1x -7 + 1x = -2 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + 1x = -2 + 0 -7 + 1x = -2 Add '7' to each side of the equation. -7 + 7 + 1x = -2 + 7 Combine like terms: -7 + 7 = 0 0 + 1x = -2 + 7 1x = -2 + 7 Combine like terms: -2 + 7 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| ln(5x-12)=9 | | Y-a=26 | | n^2-2n-3=6 | | x^2+6x=130 | | (3+2i)(3+2i)=0 | | 10m=k^2 | | 4g+3=23 | | X^2+5-104=0 | | 3n=30-3 | | x=48 | | 6x^3-13x^2-8x= | | 14=-16t^2+24t+6 | | g(b+6)=7x-2 | | 2+m=3 | | -2h+5=5h-44 | | N^2+10=-5n | | 5n=26+4 | | 6x=11x^2 | | -5h+6=41 | | x-10+x+30=120 | | 3x+=5x-1 | | 2(7x-55)=7x-20-2x | | x-10=120 | | 4x+2(x+5)-3x=3x+20 | | 0=x^2-8x-4 | | g(7b)=7x-2 | | -3=-t^3+5t^2-2t | | 6x+17+x=-74 | | sin(5x)+cos(5x)=0 | | x*z=y*z | | 9=t^3-5t^2+2t | | 16-5(2m+8)= |